2013
DOI: 10.1016/j.nbd.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Anti-epileptogenesis: Electrophysiology, diffusion tensor imaging and behavior in a genetic absence model

Abstract: The beneficial effects of chronic and early pharmacological treatment with ethosuximide on epileptogenesis were studied in a genetic absence epilepsy model comorbid for depression. It was also investigated whether there is a critical treatment period and treatment length. Cortical excitability in the form of electrical evoked potentials, but also to cortico-thalamo-cortical network activity (spike–wave discharges, SWD and afterdischarges), white matter changes representing extra corticothalamic functions and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…The network understanding gained through fMRI has also guided potential therapeutic interventions for restoring consciousness during focal seizures through electrical or optogenetic stimulation of subcortical arousal systems . BOLD fMRI with electrophysiologic verification and diffusion‐tensor imaging (DTI) have also yielded crucial insights into mechanisms of seizure generation as well as developmental epileptogenesis and epilepsy prevention …”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The network understanding gained through fMRI has also guided potential therapeutic interventions for restoring consciousness during focal seizures through electrical or optogenetic stimulation of subcortical arousal systems . BOLD fMRI with electrophysiologic verification and diffusion‐tensor imaging (DTI) have also yielded crucial insights into mechanisms of seizure generation as well as developmental epileptogenesis and epilepsy prevention …”
Section: Animal Studiesmentioning
confidence: 99%
“…42,43 BOLD fMRI with electrophysiologic verification and diffusion-tensor imaging (DTI) have also yielded crucial insights into mechanisms of seizure generation 38,44,45 as well as developmental epileptogenesis and epilepsy prevention. [46][47][48][49] | 1297 WYKES Et al.…”
Section: Bold Signals During Fmrimentioning
confidence: 99%
“…On the other hand, the antiepileptogenic effects of chronic ETX was accompanied by a decrease in depressive-like behaviour in WAG/Rij rats (Sarkisova et al, 2010;van Luijtelaar et al, 2013). Considering that epileptogenesis and chronic ETX treatment inducing antiepileptogenesis might affect mood and cognitive processes such as learning and memory, these latter processes were additionally investigated in a cue discrimination learning task in an Y-maze (problem solving task) and in a sucrose motivation task during and after chronic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The number, but not duration, of the SWDs was found to be markedly suppressed during 3 months of sequential recordings performed after termination of treatment, revealing an antiepileptogenic potential of ethosuximide. This observation has been reproduced in subsequent studies [17,31] and extended to another genetic animal model for human absence epilepsy-the GAERS rat [32]. Furthermore, ethosuximide also seems to prevent comorbid anxiety [32] and depression [31,33] in the genetic absence epilepsy models, based upon observations in the open field and the forced swim test, respectively.…”
Section: Ethosuximidementioning
confidence: 67%
“…Treatment duration seems of importance, as one study in WAG/Rij rats showed that treatment for 4 months was required, whereas a shorter treatment duration of 2 months was ineffective [31]. All studies with ethosuximide have so far been conducted with treatment initiated prior to onset of SWD, and have not examined whether chronic treatment initiated after the onset of SWD would also provide antiepileptogenic effects.…”
Section: Ethosuximidementioning
confidence: 99%